Experimental Demonstration of 40-Gb/s I-SC-FDM With 10G-Class Optics and Low-Complexity DSP for Next-Generation PON - Xizi Tang; Ji Zhou; Mengqi Guo; Jia Qi; Shuangyue Liu; Xuekai Xu; Yueming Lu; Yaojun Qiao (IEEE Photonics Journal)
Low cost and low energy consumption are two important issues for the upgrade of next-generation passive optical network (PON). In this paper, we experimentally demonstrated a 40-Gb/s PON downstream transmission employing interleaved single carrier frequency-division multiplexing (I-SC-FDM) modulation and joint frequency-time domain equalization. At the transmitter, low peak-to-average power ratio and low-complexity signal is generated using simplified encoding structure of phase rotation and complex-to-real transform. At the receiver, the digital signal processing is of low computational complexity since very few taps of joint equalization are needed. 10G-class optics are used both in transmitter and receiver to maintain a low-cost system. Experimental results indicate that total 28.6 dB link power budget over 20 km transmission in C-band was successfully achieved without using any optical amplifier or optical dispersion compensation fiber, which supports up to $1:256$ optical splitter ratio in PON systems. The proposed scheme is of great reference significance in the next-generation PON systems.